42nd AIAA/ASME/SAE/ASEE Joint Propulsion Conference &Amp;amp; Exhibit 2006
DOI: 10.2514/6.2006-4805
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Space Propulsion Based on the Flow-Stabilized Z-Pinch Fusion Concept

Abstract: A fusion space thruster based on the flow-stabilized Z-pinch may be possible in the near-term and provide many advantages over other fusion-based thruster concepts. The Zpinch equilibrium is classically unstable to gross disruption modes according to theoretical, numerical, and experimental evidence. However, a new stabilization mechanism has been discovered that can stabilize these modes with plasma flow. The stabilizing mechanism was developed for a Z-pinch plasma equilibrium which has an axial velocity prof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Because of the abundance of relatively low-cost nonradioactive fuel that can be stored as a solid at room temperature, we are investigating D 6 Li. Further, due to the very favorable scaling of fusion output with current [16,78], and emerging theoretical insights into the suppression of deleterious instabilities [79][80][81], we conclude that the pulsed Z pinch is the most direct route to fusion propulsion. The purpose of the following sections is not to offer a fusion propulsion design, nor offer in-depth details of particular experiments.…”
Section: Summary Of Proposed Pulsed Z-pinch Conceptmentioning
confidence: 93%
See 1 more Smart Citation
“…Because of the abundance of relatively low-cost nonradioactive fuel that can be stored as a solid at room temperature, we are investigating D 6 Li. Further, due to the very favorable scaling of fusion output with current [16,78], and emerging theoretical insights into the suppression of deleterious instabilities [79][80][81], we conclude that the pulsed Z pinch is the most direct route to fusion propulsion. The purpose of the following sections is not to offer a fusion propulsion design, nor offer in-depth details of particular experiments.…”
Section: Summary Of Proposed Pulsed Z-pinch Conceptmentioning
confidence: 93%
“…Plasma instabilities in the pinch discouraged continued research in the steady-state experiments, but short-pulsed Z pinch has shown a very favorable fusion yield scaling with peak current (∼I 4 ) [78] New theoretical insights are overcoming these Rayleigh-Taylor instabilities [79]. One of the best sustained efforts in propulsion is Shumlak et al's ZAP concept [80]. In ZAP, the pinch is stabilized by a shear flow generated by a coaxial plasma gun during the collapse of the pinch.…”
Section: H Pulsed Z Pinchmentioning
confidence: 97%
“…5) Pulsed electromagnetic propulsion devices usually use an intense surge of electrical current to create a high-speed jet of plasma 6) which can provide many advantages over the fusion-based thruster concepts and may be possible in the near-term and fusion space thruster based on the flow-stabilized Z-pinch. 7) The pulsed plasma propulsion can be generated by Z-pinch, 8) flow stabilized Z-pinch 7) and dense plasma focus. 9) The principle of linear plasma propulsion (LPP) as Z-pinch and high dense plasma focus is to run high currents through a plasma over short timescales (∼μs).…”
Section: Introductionmentioning
confidence: 99%
“…9) The principle of linear plasma propulsion (LPP) as Z-pinch and high dense plasma focus is to run high currents through a plasma over short timescales (∼μs). 7,8) Additionally, it provides many of the desired features for a fusion space thruster such as a linear device, no external field coils, high specific power, and high plasma density. It produces plasma that can be easily confined by an induced magnetic field to produce a high-density plasma column.…”
Section: Introductionmentioning
confidence: 99%
“…1,5,6 . In order to be useful in engineering analysis, simplified Z-Pinch fusion thermodynamic models are required to give propulsion engineers the quantity of plasma, plasma temperature, rate of expansion, etc.…”
Section: Z-pinch Modeling and Analysismentioning
confidence: 99%